Rancang Bangun Mesin Pengering Lantai Basah Berbasis Remote Control - Tahir, Abdul; Burhanuddin; Sirama, Sirama (Jurnal Mesin Nusantara, 2022)
The drying is a process of reducing to remove a certain amount of water in a material or place contains water. Drying process will not be maximized if tools used are still conventional, we need a machine to help for drying process effectively and efficiently. This research was conducted to provide a solution for the floor drying process, by designing and manufacturing a drying machine using a remote control. The method used in this study is an experimental method, carried out in several stages starting with data collection and literature study, next stage is to make a design drawing, determine the materials and materials needed, carry out the manufacturing process, assemble the control system, carry out assembly and finally carry out a machine test. The design of this machine uses a 12V DC motor drive system, equipped with a water pusher (wiper) and a mop device made of microfiber material. Machine uses an energy source from a battery with a capacity of 12V,12A. Machine is controlled using a remote control assembled from arduino. The last stage of this research is to conduct a test to determine the performance, the test is carried out on the driving motor (forward, backward, turn left, and turn right), the wiper movement (up and down), and the pel rotation. A machine made has dimensions of 810 cm long, 550 cm wide and 200 cm high .Results of the machine testing process can be concluded that the machine can run.